Design and optimization of candesartan loaded self-nanoemulsifying drug delivery system for improving its dissolution rate and pharmacodynamic potential - Ravinder Verma; Deepak Kaushik (Taylor & Francis Group, 2020)
During the last decades, much attention has been focused on SNEDDS approach to resolve concerns of BCS II class drugs with accentuation on upgrading the solubility and bioavailability. The present hypothesis confirms the theory that SNEDDS can reduce the impact of food on Candesartan solubilization, thereby offering the potential for improved oral delivery without co-administration with meals. The present studies describe quality-by-design-based development and characterization of Candesartan loaded SNEDDS for improving its pharmacodynamic potential. D-optimal mixture design was used for systematic optimization of SNEDDS, which showed globule size of 13.91 nm, more rapid drug release rate of >90% in 30 min and 16 s for self-emulsification. The optimized formulations were extensively evaluated, where an in vitro drug release study indicated up to 1.99- and 1.10-fold enhancement in dissolution rate from SNEDDS over pure drug and marketed tablet. In vivo pharmacodynamic investigation also showed superior antihypertensive potential of SNEDDS in normalizing serum lipid levels as compared to pure drug and marketed tablet that was executed on male Wistar rats. Overall, this paper reports successful systematic development of candesartan-loaded SNEDDS with distinctly improved biopharmaceutical performance. This research work interpreted a major role of SNEDDS for enhancing the rate of dissolution and bioavailability of poorly water soluble drugs.